Fortifikasi Tepung Tulang Ikan Gabus (Channa striata) pada Kerupuk sebagai Sumber Kalsium - M. Ryo Andika Putra; Rodiana Nopianti; Herpandi Herpandi (Jurnal FishtecH, 2015)
The purpose of this research was to investigae of snakehead fish bone meal addition to crackers characteristic. This research was used random block design (RBD). The treatment of snakehead fish bone meal were 0%, 10%, 20%, 30%, and 40%. The parameters of this research were chemical analysis such as water, ash, protein, lipid, carbohidrate and calcium, while physic analysis such as hardness, colour, volume expands, and sensoric analysis such as colour, texture (hardness), aroma and taste. The result showed that treatment gave significant effect on ash, protein, lipid, carbohidrate and calcium, physic analysis such as hardness, volume expands, lighness and chrome, sensoric analysis such as hardness and taste, but they were no effect to water content, hue, and sensoric analysis such as colour and aroma. ash consentration of this crackers interval 2.85%-19.19%, protein was on 1.96%-6.14%, lipid was on 14.75%-19.39%, carbohidrate was on 56.05%-72.00%, calcium was on 21.60mg/100g-572.51mg/100g. The hardness of this crackers was 229.23 gf - 558.92 gf, volume expands was 45.58%-97.30%, lightness was 60.93%-71.03%, chrome was 6.33%-18.70% and hardness of analysis sensoric was 1.96-3.13 and taste was 2.01-3.24. The crackers were added with snakehead fish bone meal had effect on hardness